HYDROCRACKING OF VACUUM DISTILLATE AND LUBRICANT BASE STOCK PRODUCTION - A.S. Nasution (Scientific Contributions Oil and Gas, 1984)
Hydrocracking of vacuum distillate for middle distillate and lubricant base stock production has been carried out with temperature (from 400Â° to 420Â°). Hourly Liquid Space Velocity (from 0.422 to 0.88), Pressure (100 kg/cm2) and H2/Hydrocarbon ratio (1000 It/lt), by using a Catatest unit apparatus.